(3JYdje (B- (3JOQjH (B- (3Jbjje (B- (3JMcjes - (3aQL Gdjf hOjYs ((3GdGScfOQjIs (3efTCI GdeYGQas, 2000)
(3JWQb GdCgOGa GdJQHhjI h GdbhGYO GdCSGSjI GdNGUI HQjGVI GdJfS,YGQVG JMdjdG eaUdG ddVQHGJ GdCSGSjI h GdeJbOeI h GdCNWGA GdTGFYI ,h jTed Ydi GdCSS GdgGeI dNWW GddYH GdaQOj h GdRhLj ,bOe WQb JYde GdJfS h GdEYOGO GdHOfj GdNGU HgG ,hHYV GdfUGFM ddGYHjf GdLOO(B.s